Kajian Paparan Bahan Tambahan Pangan Benzoat pada Anak-anak Berdasarkan Data Konsumsi Pangan Individu di Kabupaten Bogor - Sarifudin, Achmat (Universitas Sebelas Maret, 2007)
Food additives exposure assessment of benzoate is one of the important points in health risk assessment. This assessment is needed to protect the children from negative impact caused by excessive consumption of benzoate. The method used to predict individual benzoate consumption by calculating all benzoate consumption contained in food product in 3 days consumption. Concentration data of benzoate in the products was determined based on assumption of highest concentration allowed by government regulation of Food Additives i.e Permenkes no. 722/Menkes/PER/IX/1988. To obtain benzoate exposure level, the sum of benzoate consumptions was compared with safety limit level of benzoate (Acceptable Daily Intake) Value. This research resulted a mean value of benzoate consumption is 0.36 mm/kg BW (Body Weight) or its exposure level 7% ADI (ADI Benzoate= 5 mg/kg BW) and even highest consumer (95th) is 1.16 mg/kg BW or its exposure level 23% ADI